Education strategy of counter-radicalism with aswaja orientation in quranic education centers in indonesia - Husna Nashihin; Yenny Aulia Rachman (At Turots: Jurnal Pendidikan Islam, 2024)
The existence of Quranic education has a fundamental goal related to the importance of introducing and instilling the values of the Quran from an early age. This field research has four research focuses: firstly, the objectives of Aswaja-oriented counter-radicalism in Quranic Education Centers (TPQ). Secondly, the competency standards of Aswaja-oriented counter-radicalism in TPQ education. Thirdly, the curriculum structure of Aswaja-oriented counter-radicalism in TPQ. The results of this research indicate that, firstly, the objectives of Aswaja-oriented counter-radicalism in TPQ education are to develop children's potential towards the formation of moderate religious attitudes and knowledge. Secondly, the curriculum of Aswaja-oriented counter-radicalism in TPQ education consists of standard curriculum components, namely, reading the Quran, writing and memorizing Quranic verses, Tajweed, and memorizing major prayers, as well as additional curriculum components on moderate religious practices. Thirdly, the curriculum structure of Aswaja-oriented counter-radicalism in TPQ education consists of seven competency standards: Quran, Tajweed, Prayer Recitation Memorization, Worship Practices, Memorization of Short Surahs, Daily Prayer Memorization, and Local Content (Aswaja Study).